2005
DOI: 10.1007/s00360-005-0028-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of grasshopper vitellogenin production in response to diet is primarily a result of changes in fat body mass

Abstract: Life history plasticity is the developmental production of different phenotypes by similar genotypes in response to different environments. Plasticity is common in early post-embryonic or adult development. Later in the developmental stage, the transition from developmentally plastic to canalized (i.e., inflexible) phases is often associated with the attainment of a threshold level of storage. Thresholds are often described simply as total body mass or cumulative consumption of food. The physiological characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…More severe food limitation in this grasshopper (30 -40% of ad libitum) reduced hemolymph protein levels by 40%, without halting reproduction; this result was highly statistically significant and was repeatable across two experiments (Hatle et al 2001;. That life-extending CR did not alter protein storage is particularly surprising for a phytophagous insect, because they are protein limited during major life history transitions (e.g., Hatle et al 2003a;Hatle et al 2006). Hence, the present results do not support the hypothesis that protein storage is involved in life extension by CR.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…More severe food limitation in this grasshopper (30 -40% of ad libitum) reduced hemolymph protein levels by 40%, without halting reproduction; this result was highly statistically significant and was repeatable across two experiments (Hatle et al 2001;. That life-extending CR did not alter protein storage is particularly surprising for a phytophagous insect, because they are protein limited during major life history transitions (e.g., Hatle et al 2003a;Hatle et al 2006). Hence, the present results do not support the hypothesis that protein storage is involved in life extension by CR.…”
Section: Discussionmentioning
confidence: 73%
“…These CR diets significantly increased longevity but did not alter tactics of the first clutch. This interesting result calls for further studies to determine if these patterns of longevity and reproductive output hold in the wild, and whether other storage parameters, such as fat body mass (shown to be most important in reproductive plasticity by Hatle et al 2006), are affected by these diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that JH may not be the only factor involved in the regulation of vitellogenin production, but instead some other nutrition-dependent change is needed. Similarly, Hatle et al found that total vitellogenin production relies more on total fat body mass than on massspecific tissue stimulation (typically by JH) (Hatle et al, 2006a). This suggests that growth factors affecting the fat body, which are likely nutrition dependent, might be a co-requirement with JH for vitellogenesis (Hatle et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hatle et al found that total vitellogenin production relies more on total fat body mass than on massspecific tissue stimulation (typically by JH) (Hatle et al, 2006a). This suggests that growth factors affecting the fat body, which are likely nutrition dependent, might be a co-requirement with JH for vitellogenesis (Hatle et al, 2006a). Hence, studies on vitellogenin production suggest threshold feeding is needed both to initiate production of JH and to bring about competence to JH.…”
Section: Introductionmentioning
confidence: 99%